Ultrastructural alterations in the gills of cyprinid, Labeo rohita (Hamilton) exposed to Lead nitrate (Indian Journal of Experimental Biology (IJEB), 2021)
Lead contaminates aquatic ecosystems and causes deleterious effects on aquatic organisms, particularly fishes, and percolates to human beings through food chain as accumulated residue. In this context, we conducted histological studies on impact of lead toxicity in Rohu, Labeo rohita (Hamilton), a common freshwater fish consumed by humans, exposed to sub-lethal concentrations of lead nitrate. Previously, we observed damage in the gills using light microscope, and now we studied ultrastructural alterations at cellular level in the gills using Transmission electron microscopy (TEM). The gill tissues were dissected after 15, 30, 45 and 60 days of exposure, washed, fixed in Karnovsky's fixative, and processed further for histological investigation. Normal cellular architecture was noticed in the control group while, whereas large number of alterations could be observed in different organelles in the cells of the lead nitrate treated groups. The severity of the lesions was proportional to the increased concentration of the tested pollutant in a time dependent manner.